The Relationship of Nutmeg Populations from Tidore, Ternate, and Bogor Based on Morphological Marker - Tias Arlianti; Desta Wirnas; NFN Sobir; Otih Rostiana (Buletin Penelitian Tanaman Rempah dan Obat, 2019)
Banda Nutmeg (Myristica fragrans), is one of Indonesia's main spices commodities. Maluku Island, North Maluku, Siau, and Papua are the center of origins and center of nutmeg diversity; whereas, Bogor is the largest nutmeg cultivation area in West Java. The diversity and relationship between Bogor nutmeg with Maluku nutmeg have not been studied, even though it is crucial for local varieties selection and seeds provision. The study aimed to determine the diversity and relationship of nutmegs from Tidore, Ternate, and Bogor. The experiment was conducted in eight locations: Tidore (Gurabunga and Jaya), Ternate (Marikurubu), and Bogor (Cigombong, Ciawi, Leuwisadeng, Sukajadi, and Tamansari) from November 2017 - December 2018. Materials used were 46 nutmeg accessions of 8 – 30 year old plants with good growth and known of their origin. The experiments were performed using direct observation methods on habitus, leaf, fruit, seed, mace,  and flower followed IPGRI descriptor.  The results showed that qualitative diversity was observed in the fruit shape, shape of fruit-based and fruit-tip, fruit color, and tree shape. Mace thickness was the most substantial diversity for the quantitative character (50.38 %). The difference within intra-population in all aspects observed was low, except for the fruit character and mace weight. The genetic relatedness of the Bogor population was closer to Ternate (60 %) than Tidore (46 %). The genetic relationship amongst five Bogor populations found to be very close. Further, Leuwisadeng, Tamansari, and Sukajadi populations were found to have the highest genetic relationship and similarity (80 %).